غیرت کے نام پر قتل: اسلامی تعلیمات، سماجی عوامل اور تدارکی حکمتِ عملی کا تحقیقی و تجزیاتی جائزہ: Honor Killing in the Name of “Ghairat”: An Analytical Study of Islamic Teachings, Socio-Cultural Factors, and Preventive Strategies (Al-Aasar, 2025)
Honor killing is one of the gravest forms of gender-based violence, deeply rooted in patriarchal structures, rigid cultural traditions, and weak law enforcement. It involves the murder of a family member—most often women—under the pretext of preserving “honor.” In Pakistan, it is referred to by various local terms such as Karo Kari, Kala Kali, and Siah Kari. Victims are usually accused of having illicit relations, rejecting forced marriages, or exercising their right to choice in marriage. In many instances, women are killed based on suspicion, false allegations, or even after surviving sexual assault. The Human Rights Commission of Pakistan reported 392 cases of women killed in the name of honor between January and November 2024. From the Islamic perspective, “ghairat” (self-respect, modesty, dignity) is indeed a noble quality, but Islam strictly prohibits injustice and the unlawful taking of life. The Qur’an and Sunnah emphasize justice, mercy, and the sanctity of human life. Therefore, honor killing is an un-Islamic practice that contradicts Islamic values.This article analyzes honor killing through three dimensions: the Islamic stance on ghairat and murder, socio-cultural and legal factors contributing to this crime, and practical measures to counter this injustice. It highlights the necessity of societal reforms, strict enforcement of laws, public awareness campaigns, and revival of Islamic principles of justice and compassion. The study concludes that only through collective efforts—combining legal, social, and religious frameworks—can this practice be eradicated.